HUBUNGAN BEBAN KERJA MENTAL DENGAN KELELAHAN KERJA PADA TENAGA KEPERAWATAN DAN TENAGA KEBIDANAN DI PUSKESMAS MLATI II SLEMAN YOGYAKARTA - Ardiyanti, Nofia; Wahyuni, Ida; Suroto, Suroto; Jayanti, Siswi (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Work fatigue is a reduction in work capacity and endurance due to personal or physiological factors which may lead to decreased alertness, concentration and thoroughness resulting in accidents at work. Each job includes work load, both physical and mental, depending on workers' skill level, physical fitness, nutritional status, sex, age, and body size. This study aims to determine the relation of mental workload, history of disease, nutritional status, work period, age, and sex with work fatigue in nursing and midwifery personnel at Mlati II Public Health Center in Sleman, Yogyakarta. This study is conducted in mix methods (combination of quantitative and qualitative study). The population of this study are nursing and midwifery personnel in number of 21 persons, with sampled is total population. In depth interview was conducted on 3 respondents with very tired fatigue level and respondents wtih very high mental workload. Work fatigue rates were measured using reaction timer device and in depth interview, mental workloads using NASA TLX questionnaire and in depth interview and nutritional status with Body Mass Index (BMI) measurements. The measurement of work fatigue and mental workload were supported by in-depth interview. Statistical analysis using Rank Spearman test resulted in significant relationship between mental work load with work fatigue (p=0.013), nutritional status (p=0.022), and age (p=0.034). In addition, the study showed no correlation between disease history and work fatigue (p=0.172), length of service (p=0.236), and sex (p= 0.095). This research recommends that respondents can take advantage f the rest time by listened to light music to relax the mind.